Comparison of Gene Expression Profiles of Uropathogenic Escherichia Coli CFT073 after Prolonged Exposure to Subinhibitory Concentrations of Different Biocides - Małgorzata Ligowska-Marzęta; Viktoria Hancock; Hanne Ingmer; Frank M. Aarestrup (MDPI AG, 2019)
Biocides are chemical compounds widely used for sterilization and disinfection. The aim of this study was to examine whether exposure to subinhibitory biocide concentrations influenced transcriptional expression of genes that could improve a pathogen’s drug resistance or fitness. We used DNA microarrays to investigate the transcriptome of the uropathogenic Escherichia coli strain CFT073 in response to prolonged exposure to subinhibitory concentrations of four biocides: benzalkonium chloride, chlorhexidine, hydrogen peroxide and triclosan. Transcription of a gene involved in polymyxin resistance, arnT, was increased after treatment with benzalkonium chloride. However, pretreatment of the bacteria with this biocide did not result in cross-resistance to polymyxin in vitro. Genes encoding products related to transport formed the functional group that was most affected by biocides, as 110 out of 884 genes in this category displayed altered transcription. Transcripts of genes involved in cysteine uptake, sulfate assimilation, dipeptide transport, as well as cryptic phage genes were also more abundant in response to several biocides. Additionally, we identified groups of genes with transcription changes unique to single biocides that might include potential targets for the biocides. The biocides did not increase the resistance potential of the pathogen to other antimicrobials.